2005
DOI: 10.2337/diacare.28.12.2890
|View full text |Cite
|
Sign up to set email alerts
|

Serum Interleukin-18 Levels Are Associated With Nephropathy and Atherosclerosis in Japanese Patients With Type 2 Diabetes

Abstract: OBJECTIVE -Interleukin (IL)-18 is a proinflammatory cytokine secreted from mononuclear cells. Serum concentration of IL-18 is a strong predictor of death in patients with cardiovascular diseases. Recent studies have shown that microinflammation is involved in the pathogenesis of diabetic nephropathy as well as of cardiovascular diseases. This study aimed to test the hypothesis that the serum level of IL-18 is a common predictor of nephropathy and atherosclerosis in patients with type 2 diabetes.RESEARCH DESIGN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
139
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(155 citation statements)
references
References 41 publications
13
139
0
3
Order By: Relevance
“…The present findings for IL-18 examined in a long-term follow-up study extend the findings of previous crosssectional association studies in patients with type 1 and type 2 diabetes mellitus [17][18][19]. Nakamura et al reported that serum and urinary IL-18 levels in Japanese patients with type 2 diabetes mellitus correlated positively with urinary AER at baseline and after 6 months, a relatively short period [19].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The present findings for IL-18 examined in a long-term follow-up study extend the findings of previous crosssectional association studies in patients with type 1 and type 2 diabetes mellitus [17][18][19]. Nakamura et al reported that serum and urinary IL-18 levels in Japanese patients with type 2 diabetes mellitus correlated positively with urinary AER at baseline and after 6 months, a relatively short period [19].…”
Section: Discussionsupporting
confidence: 78%
“…Nakamura et al reported that serum and urinary IL-18 levels in Japanese patients with type 2 diabetes mellitus correlated positively with urinary AER at baseline and after 6 months, a relatively short period [19]. Our longer observational follow-up study clearly showed a prognostic impact of serum IL-18 levels on the future development of microalbuminuria.…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, elevated IL-18 serum levels were reported in patients with type 1 diabetes complicated by nephropathy [26]. Other authors have also demonstrated increased IL-18 serum levels in relation to the presence of persistent complications in the course of type 2 diabetes [12].…”
Section: Discussionmentioning
confidence: 84%
“…In pathological conditions, IL-18 is involved in angiogenesis [10], arteriosclerosis [11], tissue destruction, and seems to play a role in the autoimmune b-cell destruction [12]. Recent studies have shown that circulating IL-18 may be a predictor of progression of diabetic nephropathy as well as cardiovascular diseases [13].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, IFN-γ secretion by T-cells can initiate and further accelerates inflammation by the activation of macrophages and vascular cells and exacerbation of oxidative stress within renal tissues [32,16]. Besides, IL-18 levels increase in diabetic patients with the development of urinary albumin excretion [64]. So, elevated urinary excretion levels of IL-18 reported in patients with diabetic nephropathy seems to be closely related to the progression of diabetic nephropathy [63].…”
Section: Cytokines and Chemokinesmentioning
confidence: 99%